Blockchain and cloud computing-based secure electronic healthcare records storage and sharing - Amanat, Amna; Rizwan, Muhammad; Maple, Carsten; Zikria, Yousaf Bin; Almadhor, Ahmad S.; Kim, Sung Won (Frontiers in Public Health, 2022)
Healthcare information is essential for both service providers and patients. Further secure sharing and maintenance of Electronic Healthcare Records (EHR) is imperative. Blockchain is a distributed, decentralized ledger technology that can provide secured, validated, and immutable data sharing facilities. EHR systems in healthcare have traditionally relied on a centralized system (e.g., cloud) for exchanging health data across healthcare stakeholders and that may expose private and sensitive patient information. EHR has struggled to meet the demands of several stakeholders and systems in terms of safety, isolation, and other regulatory constraints. Blockchain creates a distributed ledger system using techniques of cryptography (hashes) that are consistent and permit actions to be carried out in a distributed manner without the need for a centralised authority. Data exploitation is difficult and evident in a blockchain network due to its immutability. We propose an architecture based on blockchain technology that authenticates the user identity using a Proof of Stake (POS) cryptography consensus mechanism and Secure Hash Algorithm (SHA256) to secure EHR sharing among different electronic healthcare systems. An Elliptic Curve Digital Signature Algorithm (ECDSA) is used for the verification of EHR sensors to assemble and transmit data to cloud infrastructure. Results indicate that the proposed solution performs extremely well when compared with existing solutions, which include Proof-Of-Work (POW), Secure Hash Algorithm (SHA-1) and Message Digest (MD5) in terms of power consumption, authenticity, and security of healthcare records.